The singular molecular conformation of humic acids in solution influences their ability to enhance root hydraulic conductivity and plant growth - Olaetxea, Maite (2020)
Some studies have reported that the capacity of humic substances to improve plant growth is dependent on their ability to increase root hydraulic conductivity. It was proposed that this effect is directly related to the structural conformation in solution of these substances. To study this hypothesis, the effects on root hydraulic conductivity and growth of cucumber plants of a sedimentary humic acid and two polymers-polyacrylic acid and polyethylene glycol-presenting a molecular conformation in water solution different from that of the humic acid have been studied. The results show that whereas the humic acid caused an increase in root hydraulic conductivity and plant growth, both the polyacrylic acid and the polyethylene glycol did not modify plant growth and caused a decrease in root hydraulic conductivity. These results can be explained by the different molecular conformation in water solution of the three molecular systems. The relationships between these biological effects and the molecular conformation of the three molecular systems in water solution are discussed.